2020
DOI: 10.1007/s00167-020-06150-x
|View full text |Cite
|
Sign up to set email alerts
|

CT-based patient-specific instrumentation for total knee arthroplasty in over 700 cases: single-use instruments are as accurate as standard instruments

Abstract: Purpose Efforts in total knee arthroplasty are made to improve accuracy for a correct leg axis and reduce component malpositioning using patient-specific instruments. It was hypothesized that use of patient-specific instruments (vs. computernavigated and conventional techniques) will reduce the number of outliers. Our second hypothesis was that single-use instrumentation will lead to the same accuracy compared to patient-specific instruments made of metal. Methods 708 primary total knee arthroplasties between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…Our results demonstrated a 19.6% and 7.8% rate of outliers outside the 2° and 3° target zones, respectively. Our results remain better than those found in the literature using conventional instruments [ 27 , 28 ], and are close to the best results found with custom cutting guides [ 29 ]. Levengood et al demonstrated a lower rate of 2° outliers, at 15.8% [ 30 ].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Our results demonstrated a 19.6% and 7.8% rate of outliers outside the 2° and 3° target zones, respectively. Our results remain better than those found in the literature using conventional instruments [ 27 , 28 ], and are close to the best results found with custom cutting guides [ 29 ]. Levengood et al demonstrated a lower rate of 2° outliers, at 15.8% [ 30 ].…”
Section: Discussionsupporting
confidence: 85%
“…Our results align closely with their excellent findings for navigation. Studies investigating CIM cutting guide shows slightly lower rate of 3° outliers: with Gaukel et al reporting 2.3% [ 29 ] while Sariali et al reported a perfect rate of 0% [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Koch et al [26] reported a total of 12.4% of outliers in the frontal plane in 291 cases. Other studies of CT‐based PSI‐TKA showed comparable low outlier rates [27, 28]. This might be due to the surgeon dependent adjustment to the PSI cutting jigs of the 3D models and/or intraoperative corrections.…”
Section: Discussionmentioning
confidence: 87%
“…Despite a number of studies 4 demonstrating no benefit associated with PSI in enhancing mechanical axes and implant survival, a review study in 2022 revealed the notable accuracy of CT-based PSI for mechanical leg axes and postoperative knee angles in over 700 cases 5 . Moreover, there is considerable research examining the efficacy of PSI in a variety of other contexts.…”
Section: Discussionmentioning
confidence: 99%